The application of the inquiry-based teaching model in teaching dermatology and venereology - ZHOU Ying; DOU Shuhui (Pifu-xingbing zhenliaoxue zazhi)
Dermatovenereology is a multidisciplinary and interdisciplinary subject. In exploration of modern teaching models, the inquiry-based teaching model is proved to assist students in accurately and efficiently mastering the disciplinary knowledge which they have learned on the basis of giving full play to their subjective initiative, and its significance for this discipline is self-evident. This paper systematically expounds the practical value of the inquiry-based teaching model from multiple aspects such as connotation, characteristics, and significance. It is reasonable to believe that the inquiry-based teaching model, as one of the modern teaching models, can effectively help students understand, master, and apply knowledge in practice, truly enabling them to grow through learning, to improve through practice, and to apply what they have learned.